Development of Interactive E-Worksheet Based on Gamification to Improve Digital Literacy of Junior High School Students - Fitrianingsih, Nur; Sani , Khairul; Fitriati , Ita; Shandi , Shutan Arie (FKIP - Universitas Riau, 2025)
This research aimed to develop an interactive electronic student worksheet (E-LKPD) based on gamification to enhance the digital literacy of junior high school students. The study was conducted using a Research and Development (R&D) design with the ADDIE model, involving stages of analysis, design, development, implementation, and evaluation. The product was validated by experts in media and material, obtaining feasibility percentages of 92% and 90% respectively, which were categorized as